Antineoplastic Mechanism of Emblica Officinalis Against Breast Cancer, A Humans Clinical Cross Sectional Study - Shuja, Naveed; Ansari, Mashkoor Ahmed; Phull, Qamar Zaman; Sodhar, Jawad Mumtaz; Shuja, Arslan; Maqsood, Majida (Pakistan Journal of Medical & Health Sciences, 2022)
Current study was found that there is a significant changes (<0.005) were observed in both groups regarding reoccurrence of malignancy by considering their MRI and bone scan with passage of time. There were 70 women with breast cancer in Group B and 30 in Group A. 10 g/day emblica officinalis extract was given to the individuals of group B orally for two years their preoperative and Postoperative levels of MRI and bone scan mean standard deviation were (1.81±0.1),(clear) and (0.00±0.00.00±0.0, 0.00±0.0, 0.00±0.0), (clear, all) after 6,12,18 and 24 months respectively, while in Group A, there were 30 women with breast cancer their preoperative and postoperative levels MRI and bone scan mean standard deviation levels were (1.91±1.1), (clear) and (0.12±0.0, 0.70±0.1, 0.93±0.2, 1.00±0.0), (clear, all) after 6,12,18 and 24 months respectively.